KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGEMBANGKAN BUDAYA ISLAM - Abdullah Khanif (Institut Agama Islam Uluwiyah Mojokerto, 2020)
Principal Leadership in Developing a Culture of Islam (Case Study In SMP Islam Al-Azhar Kota Mojokerto Keywords: Principal Leadership, Development of Islam Culture Islam culture in SMP IslamAl-Azhar Mojokerto city was describing is that the community (residents) Schools are not the teachings and religious values are maximum in everyday life. Life in the school environment has not given the life style in accordance with Islamic teachings, tried to escort the Principal and urge all citizens have agreed to create a culture of Islam in the schools and trying to do as much as possible. In everyday life is not all citizens to practice the values of Islam, as Islam culture in the school such as: (a) The civilizing greetings for residents / Community Schools (b) Activities not maximum congregational Salat is performed. (C) Dressing with Muslims is not in line with expectations. (D) Less realized the meaning of living a healthy and clean environment (e) Cultural Shadaqoh can not be applied optimally (f) Cultural Dhuha prayer performed maximal (g) Not all students can read Al-Qur'an, whether or mujawwad murottal. (H) pray before and after the lesson has not been maximally implemented. (I) Lack of awareness of citizens on the Implementation IMTAQ together. (J) The number of students who do not obey school rules and regulations. (k) Valuing and respecting other people still need to be improved. Based on the existing problems on this research seeks to reveal the principal's leadership in developing the religious culture in SMP Islam Al-Azhar Mojokerto city, with a sub focus of research (1) describing the values of Islam that developed in the school community, (2) describe the role of principal leadership and efforts in realizing religious values, (3) describing the response of residents towards the development of schools of Islamic culture.